PENGARUH PEMBERIAN JUS BAYAM MERAH TERHADAP PENINGKATAN KADAR Hb IBU HAMILTRIMESTER III DI PUSKESMAS PINGGIR KECAMATAN PINGGIR KABUPATEN BENGKALIS - Agustina, Santi; Diana, Nana (Ensiklopedia of Journal, 2025)
During pregnancy, there is an increase in blood volume (hypervolemia) in pregnant women, which requires an adequate supply of iron during pregnancy. Pregnant women who suffer from anemia have the opportunity to experience bleeding during childbirth. The most common cause of anemia is deficiency of nutrients such as folic acid and vitamin B12, and about 75% of anemia in pregnancy is caused by iron deficiency. One way to be able to fulfill iron can be done by consuming lots of vegetables, one of which is red spinach. Red spinach is a plant that contains vitamin C, folic acid and iron so that it can prevent anemia in pregnant women. This study aims to determine the effect of red spinach jus  on hemoglobin levels in third trimester pregnant women at Pinggir Public Health Center, Pinggir District, Bengkalis Regency. This research was conducted in Agustus 2024. The design of this study was to use the One group pre test post test design. Samples were taken using purposive sampling. The number of samples as many as 20 people. Measurement of Hemoglobin Levels using Hb test. Giving red spinach jus once a day as much as 100 ml  for 14 days. The results of the dependent T test showed that the average hemoglobin level increased from 9.765 to 10, 870  with a difference of 1.10 g/dl. Bivariate analysis showed that the results of the t-dependent statistical test were obtained (p = 0.000) < (0.05) so that red spinach jus had an effect on increasing the frequency of Hb in third trimester pregnant women at Pinggir Public Health Center, Pinggir District, Bengkalis Regency.Consuming red spinach jus is expected to prevent anemia in pregnant women which is useful in the growth and development of the fetus during pregnancy. Keywords: anemia, pregnancy, red spinach jus